The angiotensin II type 1 receptor blocker olmesartan preferentially improves nocturnal hypertension and proteinuria in chronic kidney disease - Yanagi, Mai (2012)
Accumulated evidence suggests that an altered ambulatory blood pressure (BP) profile, particularly elevated nighttime BP, reflects target organ injury and is a better predictor of further cardiorenal risk than the clinic BP or daytime BP in hypertensive patients complicated by chronic kidney disease (CKD). In this study, we examined the beneficial effects of olmesartan, an angiotensin II type 1 receptor blocker (ARB), on ambulatory BP profiles and renal function in hypertensive CKD patients. Forty-six patients were randomly assigned to the olmesartan add-on group (n=23) or the non-ARB group (n=23). At baseline and after the 16-week treatment period, ambulatory BP monitoring was performed and renal function parameter measurements were collected. Although the baseline clinic BP levels and the after-treatment/baseline (A/B) ratios of clinic BP levels were similar in the olmesartan add-on and non-ARB groups, the A/B ratios of ambulatory 24-h and nighttime BP levels in the olmesartan add-on group were significantly lower. Furthermore, the A/B ratios of urinary protein, albumin and type IV collagen excretion in the olmesartan add-on group were significantly lower than those in the non-ARB group (urinary protein excretion, 0.72±0.41 vs. 1.45±1.48, P=0.030; urinary albumin excretion, 0.73±0.37 vs. 1.50±1.37, P 0.005; urinary type IV collagen excretion, 0.87±0.42 vs. 1.48±0.87, P=0.014) despite comparable A/B ratios for the estimated glomerular filtration rate in the two groups. These results indicate that in hypertensive patients with CKD, olmesartan add-on therapy improves the ambulatory BP profile via a preferential reduction in nighttime BP with concomitant renal injury inhibition.